Job creation, job destruction and reallocation in Sub-Saharan Africa: Irm-level evidence from Kenyan manufacturing sector - Stephen Esaku (Cogent Economics & Finance, 2020)
Is the poor aggregate employment growth of the manufacturing sector in Sub-Saharan African countries the outcome of inadequate job creation or rival forces of job creation and job destruction acting in opposite direction? Using a unique dataset from the Kenyan manufacturing sector, we examine this question using ordinary least squares method and feasible generalized least squares technique. We find simultaneous high rates of job creation and job destruction. In most cases, job creation in the manufacturing sector was not adequate to offset the rapid destruction of jobs. Second, we find that the presence of simultaneously high rates of job creation and job destruction cut across firm size and age. Third, we find that young firms account for almost all of the net job creation rates implying that the firm's age is important in shaping its contribution to net job creation rates. Our findings have practical implications. First, job creation policies alone without policies that mitigate the destruction of jobs created might not be successful. For job creation to be successful in the manufacturing sector, effort should be made towards developing strategies that mitigate the destruction of jobs created. This is because job creation and destruction rates simultaneously follow each other. Second, to expand employment growth, effort should be dedicated to supporting young firms (6-10 years), through possibly, tax relief, providing technology of production or any possible government subsidy that can help these firms grow and survive in the turbulent business environment.
Keywords: E24; J23; L25; L26; 330; employment; job creation; firm performance; entrepreneurship